PERENCANAAN DAN PELAKSANAAN ALOKASI DANA DESA (ADD) DI DESA PENGALIHAN KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR TAHUN 2017-1018 - Ari Agus Pratama; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Village Government has a significant role in managing Village Fund Allocation. The main task that must be carried out by the government / village apparatus is how to carry out the process of planning and implementing Village Fund Allocation on target and useful for the progress of the village. However, in its implementation there must be things that become obstacles to achieving the implementation of all the planning properly.This study aims to determine, plan and implement the D Village Fund Allocation for the Development of the Village Transfer, Enok District, Indragiri Hilir Regency. Research uses management theory, roles, implementation and village planning. Primary information sources (informants) are determined by purposive sampling and the necessary data are collected by interview techniques and literature study. The parties who succeeded in becoming the resource persons in this study were all village officials starting from the village head to the smallest village apparatus to run the ADD together.From the results of this study it can be seen that almost all planning is said to run smoothly in planning and implementation. All proceeds from village development that receive ADD funds. But still there are obstacles so far, the most visible problem is the disbursement of Funds Allocation Funds. But this has become the rules and procedures in force from the government. The role of the village government and village management so far has been very good in using ADD, starting from planning to accountability for each ADD implementation. Keywords: Role, Village Governance, Planning and Implementation